ANALYSIS OF SCHOOL-BASED MANAGEMENT AT MTS OF BALPETU VILLAGE, KEPALA MADAN DISTRICT, SOUTH BURU REGENCY - Lamatokang, Monalisa; Alhamid, Rugayah; Patty, Julia Theresia (Program Studi Ilmu Administrasi Negara FISIP UNPATTI, 2024)
This study aims to analyze the implementation of School-Based Management (SBM) at Madrasah Tsanawiyah (Mts) in Balpetu Village, Kepala Madan District, South Buru Regency. Although the SBM concept is designed to provide autonomy to schools in resource management, this study identifies significant challenges in its implementation. The main challenges faced include financial limitations, a lack of qualified human resources, inadequate infrastructure, and minimal support from the local community and government. The limited educational facilities, such as buildings still using basic construction materials, as well as restricted electricity and internet access, further hinder the learning process. Additionally, operational funds sourced from the BOS program remain insufficient to meet the school's needs. This research employs a qualitative method, with data collected through interviews, observations, and document studies. Based on the findings, it is recommended that the local government and the Ministry of Religious Affairs pay more attention to the educational conditions in this area and provide adequate support to address the issues faced. This is essential to ensure optimal learning quality and achieve the desired educational goals. This research is expected to serve as a reference for developing school-based education policies in remote areas.